Ukrainian Folklore: Historical and Artistic Aspects - Bukhnieva, Olena; Chen, Wang (Journal of Danubian Studies and Research, 2023)
In all historical periods, cultural traditions of ethnic groups occupied a central place in the educational process. Different types of folklore creativity determined the moral and aesthetic potential of each ethnic group. Today, the modern concept of art pedagogy is largely based on the widespread use of folk art heritage. Our country is a multinational and multicultural educational state, and the guarantee of its normal development is the unconditional consideration and development of the entire cultural diversity of the country. The most important place in the socio-cultural space is occupied by the heritage formed on the basis of the values of the ethnic culture spread throughout the territory of Ukraine. Studying and popularizing the cultural heritage of ethnic groups is the most important task of the state's cultural policy. Festive and ceremonial culture is an intangible cultural heritage that contributes to the establishment of identity, continuity and respect for cultural diversity and human creativity.